CRETACEOUS ROCKS OF MISOOL ARCHIPELAGO, INDONESIA - Fauzie Hasibuan; E Rusmana (Pusat Survei Geologi, 2007)
Cretaceous rocks of Misool Archipelago are exposed mostly on the southern part of the main island of Misool and its adjacent islets. The rocks belong to the upper part of Lelinta Formation, Facet Limestone Group (Waaf Formation and Gamta Formation), Fafanlap Formation (Yabatano Member) and lower part of Daram Formation. The age of the rocks ranges from Aptian to Maastrichtian based on their fossil content. The lithology of each formation is redescribed herein.The results show that almost the whole formations contain macrofossils such as molluscs and microfossils (foraminifera). The Gamta Formation (the oldest) is Late Berriasian to Middle Cenomanian in age based on the occurrences of Ptilorhynchia sp., Proclydonophora sp., Rotularia sp., Buchia sp .. ammonite gen. et sp. indet, coral indet., and trace fossils. Early Cretaceous is also indicated by the presence of Hibolithes gamtaensls, H. miosensis, Duvalia spp., and Belemnopsis jonkeri. Waaf Formation (Middle Cenomanian to Early Campanian) contains rich globigerinid and other microfossils, trace fossils, large Inoceramus up to 70 cm in length with oysters attached to it, and Prochlydonophora sp. But, this bivalve is very difficult to sample. The upper part of the Waaf Formation oontains abundant microfossils, probably indicating a bathyal environmenl Fafanlap Formation and its Yabatano Member contain micro and macrofossils such as Inoceramus misoliensis, I. (Cordiceramus paraheberti, I. (C.) cf. pseudoregularis, t. (Selenoceramus) sufflatus and t.haani, Durania wanneri, and burrows indet. Micraster and Hemiaster were difficult to sample, and so were minor coral and bryozoan. lnoceramus spp. which are found in the lower part of Fafanlap Formation indicate a Middle Campanian age. The microfossils range up to Maastrichtian. It can be concluded that the age of Fafanlap Formation is Late Santonian up to late Maastrichtian and at least Late Maastrichtian for the Yabatano Member. Based on the assemblage of microfossils reported by previous workers, the age of the Daram Formation in the tower part can be assumed as Late Maastrichtian.Biostratigraphic correlation of Lower Cretaceous in Indonesian Archipelago based on microfossils promising for the islands of Rote, Timor, Seram, Buru, Buton, the eastern, central and south arms of Sulawesi, Halmahera, New Guinea and perhaps Obi and eastern Kalimantan. In the upper Cretaceous, inooeramid bivalves are more common and are closely related to those of New Guinea and Madagascar.Cretaceous of the Misool Archiprelago is the most difficult part to correlate within Indonesia based on microfossils at present, but is promising in the future study. The microfauna of Misool is closely related to that of the Emscher Marl of Westfalen In Europe. Theforaminifera also resemble those of theSeweer Beds in the European Alps. The Easy Cretaceous of the upper part of the lochambel Beds of Spiti, India with the Neocosmoceras-Distoloceras Assemblage is probably correlatable with the upper part of the lelinta Formation of Misool. In Misool, however the latter is dominated bybelemnites even though similar in rock facies (chert-bearing beds). The inoceramid species trom Misool, e.g. lnoceramuscf. bererensis, I. (Cordiceramus) paraheberti and I, (C. cf. pseudoregularis are closely similar to those found inMadagascar, some perhaps beingcoospecific, and in both area indicating a Middle Campanian age.Keywords: Misool Archipelago,Cretaceous, Lelinta Formation, Gamta Formation,Waaf Formation, Fafanlap Formation, D aram Formation, inoceramids, belemniles, foraminifera